RESENHA - CATAPANO, Giovanni. L’idea di filosofia in Agostino. Subsidia Medievalia. Patavina. Padova: Il Poligrafo Casa Editrice, 2000. - Sangalli, Idalgo José; Vasconcellos, Manoel (Veritas (Porto Alegre), 2002)
Rsenha de obra